1974
DOI: 10.4039/ent106285-3
|View full text |Cite
|
Sign up to set email alerts
|

Tests With Single Injections of Methoxychlor Black Fly (Diptera: Simuliidae) Larvicides in Large Rivers

Abstract: Single 15-min injections of 0.18 to 0.24 p.p.m. of methoxychlor as an emulsifiable concentrate into the Saskatchewan River removed 75 to 99% of the larvae of Simulium arcticum Mall. from 23 to 34 km sections of the river. Stronger concentrations (0.30 to 0.31 p.p.m.) eliminated about 98% of the larvae from rapids 64 km distant and an estimated 46% at a distance of 139 km. Other kinds of aquatic larvae in exposed sites were also affected: Plecoptera to about the same degree as the Simuliidae, followed by Epheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…The first studies were reported in the 1970s and 1980s. Many of the early studies were based in Canada and focused on side effects either of aerial application of insecticides (e.g., fenitrothion) to forest environments (Eidt, 1975; Flannagan, 1973; Poirier and Surgeoner, 1988) or of experimental injections of simulium larvicides (e.g., methoxychlor or fenthion) into headwater streams (Burdick et al, 1968; Clark et al, 1987; Cuffney et al, 1984; Dosdall and Lehmkuhl, 1989; Flannagan et al, 1979; Freeden, 1974, 1975; Haufe et al, 1980; Hynes and Wallace, 1975; Wallace and Hynes, 1975; Wallace et al, 1976). They are thus not reported in Table 2 Yasuno et al (1981) studied the effects of the simulium larvicide temephos, which was experimentally added to two small tributaries of the Yamaguchi River, Japan, on invertebrate drift.…”
Section: Effectsmentioning
confidence: 99%
“…The first studies were reported in the 1970s and 1980s. Many of the early studies were based in Canada and focused on side effects either of aerial application of insecticides (e.g., fenitrothion) to forest environments (Eidt, 1975; Flannagan, 1973; Poirier and Surgeoner, 1988) or of experimental injections of simulium larvicides (e.g., methoxychlor or fenthion) into headwater streams (Burdick et al, 1968; Clark et al, 1987; Cuffney et al, 1984; Dosdall and Lehmkuhl, 1989; Flannagan et al, 1979; Freeden, 1974, 1975; Haufe et al, 1980; Hynes and Wallace, 1975; Wallace and Hynes, 1975; Wallace et al, 1976). They are thus not reported in Table 2 Yasuno et al (1981) studied the effects of the simulium larvicide temephos, which was experimentally added to two small tributaries of the Yamaguchi River, Japan, on invertebrate drift.…”
Section: Effectsmentioning
confidence: 99%
“…Ent. 108: 591-600 (1976) The larvae of Simulium arcticum Malloch in three collections from the North aska at chew an River of May and June 1969, 1971, and 1974 showed seven instars. The first instar larva possessed an egg burster and the seventh instar larva possessed separated cervical sclerites.…”
mentioning
confidence: 99%
“…The impact of methoxychlor [1,1, l-trichloro-2,2-bis(p-methoxyphenyl)ethane] in aquatic ecosystems has been extensively studied in Canada because of the chemical's importance as an agricultural insecticide as well as in the control of biting flies and other Diptera [1][2][3][4][5][6]. Several authors have reported the use of enclosures or limnocorrals to monitor the effects and impact of a number of substances in the aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%